2013
DOI: 10.1016/j.otsr.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament tear during the menstrual cycle in female recreational skiers

Abstract: Level IV. Retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 28 publications
(38 reference statements)
0
49
0
2
Order By: Relevance
“…There were 4 studies conducted in the United States (US), 20,22,23,26 1 in Austria, 44 1 in France, 33 and 1 in Denmark. 42 The studies ranged in size from 65 to 51,348 participants.…”
Section: Resultsmentioning
confidence: 99%
“…There were 4 studies conducted in the United States (US), 20,22,23,26 1 in Austria, 44 1 in France, 33 and 1 in Denmark. 42 The studies ranged in size from 65 to 51,348 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the high use of hormonal contraceptives [8,9] and the high rates of ACL injuries among female athletes, it is important for sci-entists to understand how hormonal contraceptives may affect the risk for ACL injury. There are conflicting data regarding ACL injury susceptibility and hormonal contraceptive use, with some studies concluding there are protective effects and others concluding there are not [1,[10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies examining functional movement via clinical tests have concluded that knee valgus moment is the biomechanical risk factor with the highest specificity and sensitivity to predict ACL injury [17][18][19][20]. Depending on the clinical test, a knee valgus moment of [16][17][18][19][20][21][22][23][24][25] Nm indicates a high risk of injury [18]. Additionally, it has been found that a shift in the center of mass away from the stance leg, as evidenced by a high vertical ground reaction force (GRF) when landing, results in increased knee valgus moments.…”
Section: Introductionmentioning
confidence: 99%
“…Serum estradiol concentrations peak in the ovulatory phase, which is prevented by using oral contraception, leading to constant level of serum estradiol concentrations . However, despite a more constant hormonal profile when using hormonal contraception fluctuations in ACL injury prevalence appear to persist, although the overall risk has been reported to decrease when using oral contraceptives …”
Section: Introductionmentioning
confidence: 99%